A full-scale field study for evaluation of simple analytical models of cross ventilation and single-sided ventilation. (January 2021) - Fan, S.; Davies Wykes, M.S.; Lin, W.E.; Jones, R.L.; Robins, A.G.; Linden, P.F.
Abstract: In this study, we evaluated several simple natural ventilation models of cross ventilation and single-sided ventilation with data measured in a full-scale field study in London. In the field study, the ventilation rate in a naturally ventilated office was measured using a tracer gas technique with CO2 . Internal temperatures were measured using a vertical temperature array. The external temperature, wind speed and direction were measured at a nearby weather station. In addition, a 1:200 scale model of the urban area within 300 m of the test room was built in a wind tunnel to measure the pressure coefficients. The ventilation models were evaluated with input data from two sources. Wind data from a nearby airport and pressure coefficients from the literature were used, as is common practice. Alternatively, wind data measured at the local weather station and the pressure coefficients measured from wind tunnel experiments were used. The results showed that, regardless of the input data sources, the cross-ventilation model in general gives reasonable predictions. For single-sided ventilation, several empirical models were evaluated and poor predictions were obtained using the models. We discuss ways in which models of natural ventilation might be improved in the future. Highlights: A full-scale field study in a naturally ventilated office room in London. Ventilation rates of both cross-ventilation and single-sided ventilation were measured. Wind-tunnel experiments on a reduced-scale model of the building and surroundings, measuring pressure coefficients. Measured local wind data and pressure coefficients were compared with commonly used models. Evaluation of simple analytical ventilation models were conducted.